2017
DOI: 10.1080/07924259.2017.1282890
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity and reproductive output of the caridean shrimp Periclimenes paivai associated with scyphozoan jellyfish

Abstract: Periclimenes paivai is notable for its symbiotic lifestyle with jellyfish. The objective of this study was to investigate the fecundity and reproductive output of females, and specifically to determine whether females protected in their host have a greater reproductive success than other shrimp species. All anatomical parts of the medusae were analyzed and the P. paivai individuals were separated. Among 83 females analyzed, 65 presented embryos in the first developmental stage, and 18 were in the final stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…In addition, we verified in the present study that the body size (carapace length) of P. northropi females is positively related to fecundity. This pattern agrees with studies on other caridean shrimp (e.g., [39,48,49]). In this sense, a relationship between brood and female size suggests that selective forces or constraints act on the reproductive output of the species [8,50,51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we verified in the present study that the body size (carapace length) of P. northropi females is positively related to fecundity. This pattern agrees with studies on other caridean shrimp (e.g., [39,48,49]). In this sense, a relationship between brood and female size suggests that selective forces or constraints act on the reproductive output of the species [8,50,51].…”
Section: Discussionsupporting
confidence: 92%
“…The mean embryos volume was similar to that in a population of P. northropi studied by Corey & Reid (1991) [44] and to other species of Palaemon, such as P. gravieri [12] and P. longirostris [2] ( Table 1). On the other hand, the embryo volume was higher compared to other Paleomonidae shrimp, such as Cuapetes americanus (Kingsley, 1878) [62] and shrimp of the genus Periclimenes (Costa, 1844) [44,49,57,63]. Differences in embryo volume may be related to differences in the environmental conditions, particularly salinity, of the species' habitats [64].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, this increase on the body size also contribute to a better accommodation of the ovary and egg carrying in shrimps for the Gebiidea and Axiidea infraorders (formerly belonging to the Thalassinidea infraorder) (Robles et al 2009;Poore et al 2016). Furthermore, the body size of females is positively related to its fecundity (Bauer & Martin 1991;Pandian 2016;Moraes et al 2017), a pattern that is corroborated by studies regarding the fecundity in species of genus Upogebia (Hill 1977;Dumbauld et al 1996;Yamasaki et al 2010), as well as in the results observed for U. omissa in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The egg size was smaller when compared with other larger decapod species, like Macrobrachium nipponese (Zhao et al, 2007). The fecundity rate of C. pseudogracilirostris was 100 ± 30 to 300 ± 50 which was similar with Periclimenes paivai 229.08 ± 120.04 (De Moraes et al, 2017) and very low when compared with other species like Macrobrachium vollenhovenii (Sintondji et al, 2019), where a single female can produce about 83,000 eggs.…”
Section: Discussionsupporting
confidence: 56%